Quality assessment of frozen and chilled native durian - Sevillano , Ma. Lourdes Cepe (SOTECH, 1998)
Native durian pulps packed in polyethylene wrapped polyesterene boxes were frozen (-10 degree celcius) and chilled (10 degree celcius).